Influence of the center of pressure on baropodometric gait pattern variations in the adult population with flatfoot: A case-control study - Padrón, Luis; Bayod, Javier; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta; López-López, Daniel; Casado-Hernández, Israel (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Adult flatfoot is considered an alteration in the foot bone structure characterized by a decrease or collapse of the medial arch during static or dynamic balance in the gait pattern. The aim of our research was to analyze the center of pressure differences between the population with adult flatfoot and the population with normal feet. Methods: A case-control study involving 62 subjects was carried out on 31 adults with bilateral flatfoot and 31 healthy controls. The gait pattern analysis data were collected employing a complete portable baropodometric platform with piezoresistive sensors. Results: Gait pattern analysis showed statistically significant differences in the cases group, revealing lower levels in the left foot loading response of the stance phase in foot contact time (p = 0.016) and contact foot percentage (p = 0.019). Conclusion: The adult population with bilateral flatfoot evidenced higher contact time data in the total stance phase compared to the control group, which seems to be linked to the presence of foot deformity in the adult population.